2018
DOI: 10.1182/blood-2018-99-119468
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of C3 with APL-2 Results in Normalisation of Markers of Intravascular and Extravascular Hemolysis in Patients with Autoimmune Hemolytic Anemia (AIHA)

Abstract: Background: Autoimmune hemolytic anemia (AIHA) is a rare autoimmune disease characterized by hemolysis mediated by autoantibodies directed against red blood cells (RBC). AIHA is classified as either warm (60-70%), or cold agglutinin disease (CAD, 20-25%), depending upon the temperature at which the autoantibodies show maximum binding. Warm AIHA is mediated by warm reactive autoantibodies, which are usually of the immunoglobulin G class (IgG). Almost 90% of CAD is medicated by monoclonal antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…An inhibitory molecule against C1q, ANX005, blocks classical complement activation as well as haemolysis in an in vitro sheep red cell assay [171]. Pegcetacoplan (APL-2), a subcutaneously administered peptide inhibitor of C3, is assessing the preliminary efficacy in both wAIHA and CAD [16,172].…”
Section: Cold Agglutinin Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…An inhibitory molecule against C1q, ANX005, blocks classical complement activation as well as haemolysis in an in vitro sheep red cell assay [171]. Pegcetacoplan (APL-2), a subcutaneously administered peptide inhibitor of C3, is assessing the preliminary efficacy in both wAIHA and CAD [16,172].…”
Section: Cold Agglutinin Diseasementioning
confidence: 99%
“…Clinical improvement by a hemoglobin median of 3.9g/dl was seen in a pivotal study [158]. Pegcetacoplan (APL-2) is a pegylated derivative of the cyclic tridecapeptide compstatin and inhibits C3 activation [172,223]. This viscous material requires a pump for subcutaneous administration and selectively binds to C3 and blocks the cleavage of C3 into C3a and C3b by C3 convertase.…”
Section: Predictors Of Relapsementioning
confidence: 99%
See 1 more Smart Citation
“…The C3 inhibitor, pegcetacoplan (APL-2), is a pegylated peptide designed for subcutaneous administration (150). Clinical phase 2 trials have found efficacy of pegcetacoplan in paroxysmal nocturnal hemoglobinuria as well as AIHA (151), and further studies in CAD are warranted. A high risk of infection with encapsulated bacteria might be suspected as a consequence of C3 inhibition, but thus far, clinical data have not supported this concern (150)(151)(152).…”
Section: Complement Modulationmentioning
confidence: 99%
“…Autoimmune hemolytic anemia (AIHA) is a rare complement-dependent autoimmune disease. Systemic inhibition of C3 complement components with APL-2 has been demonstrated in phase-2 open-label study against AIHA (Grossi et al 2018 ). APL-2 is in phase 3 trial for the patients with PNH, a complement-mediated disease.…”
Section: Complement Inhibitors As Potential Therapeutic Agentsmentioning
confidence: 99%